Structural Evolution of Nanophase Separated Block Copolymer Patterns in Supercritical CO2 - Tandra Ghoshal; Timothy W. Collins; Subhajit Biswas; Michael A. Morris; Justin D. Holmes (Nanomaterials, 2021)
Nanopatterns can readily be formed by annealing block copolymers (BCPs) in organic solvents at moderate or high temperatures. However, this approach can be challenging from an environmental and industrial point of view. Herein, we describe a simple and environmentally friendly alternative to achieve periodically ordered nanoscale phase separated BCP structures. Asymmetric polystyrene-b-poly(ethylene oxide) (PS-b-PEO) thin film patterns of different molecular weight were achieved by annealing in supercritical carbon dioxide (sc-CO2). Microphase separation of PS-b-PEO (16,000–5000) film patterns were achieved by annealing in scCO2 at a relatively low temperature was previously reported by our group. The effects of annealing temperature, time and depressurisation rates for the polymer system were also discussed. In this article, we have expanded this study to create new knowledge on the structural and dimensional evolution of nanohole and line/space surface periodicity of four other different molecular weights PS-b-PEO systems. Periodic, well defined, hexagonally ordered films of line and hole patterns were obtained at low CO2 temperatures (35–40 °C) and pressures (1200–1300 psi). Further, the changes in morphology, ordering and feature sizes for a new PS-b-PEO system (42,000–11,500) are discussed in detail upon changing the scCO2 annealing parameters (temperature, film thickness, depressurization rates, etc.). In relation to our previous reports, the broad annealing temperature and depressurisation rate were explored together for different film thicknesses. In addition, the effects of SCF annealing for three other BCP systems (PEO-b-PS, PS-b-PDMS, PS-b-PLA) is also investigated with similar processing conditions. The patterns were also generated on a graphoepitaxial substrate for device application.